2022
DOI: 10.1126/sciadv.ade3262
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation as a rate-determining step in catalytic gas generation reactions from liquid phase systems

Abstract: The observable reaction rate of heterogeneously catalyzed reactions is known to be limited either by the intrinsic kinetics of the catalytic transformation or by the rate of pore and/or film diffusion. Here, we show that in gas generation reactions from liquid reactants, the nucleation of gas bubbles in the catalyst pore structure represents an additional important rate-limiting step. This is highlighted for the example of catalytic hydrogen release from the liquid organic hydrogen carrier compound perhydro-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…[ 69,70 ] For the case of hydrogen release from LOHC systems by dehydrogenation, it has been shown that the reaction rate in a state where oscillatory hydrogen bubble nucleation takes place can be up to 50 times higher than a nucleation inhibited state of the same catalyst under otherwise identical conditions. [ 71 ] Moreover, the liquid holdup can influence the residence time in the catalytic section. [ 72,73 ] It is noteworthy that the reaction takes place primarily in the liquid phase, since the catalyst pellets must be wetted to maintain distillation premises.…”
Section: Methodsmentioning
confidence: 99%
“…[ 69,70 ] For the case of hydrogen release from LOHC systems by dehydrogenation, it has been shown that the reaction rate in a state where oscillatory hydrogen bubble nucleation takes place can be up to 50 times higher than a nucleation inhibited state of the same catalyst under otherwise identical conditions. [ 71 ] Moreover, the liquid holdup can influence the residence time in the catalytic section. [ 72,73 ] It is noteworthy that the reaction takes place primarily in the liquid phase, since the catalyst pellets must be wetted to maintain distillation premises.…”
Section: Methodsmentioning
confidence: 99%
“…The models for each stage are expected to be considerably varied as a result of different rate-limiting steps. For example, a study by Solymosi et al shows how nucleation to form hydrogen bubbles is the rate-determining step during the initial phases of the startup while not being important during other stages . In addition to optimizing performance, transient analyses are required to establish startup/shutdown protocols and usage guidelines for trucks, which could have practical and economic implications.…”
Section: Lohc Powertrain: Technical Designmentioning
confidence: 99%
“…Similarly, understanding the dependence of the flow of water on the porosity of the soil is crucial in environmental sciences [28]. Moreover, diverse techonlogies related to the energy transition such as blue-energy [29], hydrogen technology [30,31], electrolyzers and fuel cells [32,33], or CO 2 segregation [34] rely on the transport of (charged) chemical species across nanoporous materials.…”
Section: Introductionmentioning
confidence: 99%